2016
DOI: 10.2136/vzj2016.04.0036
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Monitoring and Numerical Flow Modeling to Quantify Drought Conditions in a Rangeland Ecosystem

Abstract: Core Ideas Soil water content data can be used for drought monitoring. Expected soil water conditions can be modeled using reanalysis climate data. Drought conditions can be inferred by comparing measured and expected soil water contents. A one‐dimensional vertical numerical model for coupled water flow and heat transport was calibrated for a mixed‐grass rangeland at the Sustainable Agricultural Research and Extension Center, Lingle, WY. The model predicted soil water content reasonably well, with a modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The variations of were associated with rainfall events > 4 mm and evaporation. The non-linear decrease of , as it has been reported in the literature (Engda et al, 2016), was also observed in this lysimeter. During rainy seasons, average ranged 0.146-0.137 cm 3 /cm 3 and its coefficient of variation ranged between 38.4 and 40.0%.…”
Section: Soil Water Contentsupporting
confidence: 87%
“…The variations of were associated with rainfall events > 4 mm and evaporation. The non-linear decrease of , as it has been reported in the literature (Engda et al, 2016), was also observed in this lysimeter. During rainy seasons, average ranged 0.146-0.137 cm 3 /cm 3 and its coefficient of variation ranged between 38.4 and 40.0%.…”
Section: Soil Water Contentsupporting
confidence: 87%
“…The reader is directed to Engda et al. (2016) and Fullhart et al. (2018, 2019) for more detail on the development and implementation of this method, but we include an abbreviated description of the process.…”
Section: Methodsmentioning
confidence: 99%
“…This method implicitly accounts for the presence of coarse fragments in the subsurface to allow for the development of effective hydraulic properties that include the effects of coarse fragments that may be missed when calibrating water retention parameters directly. In Engda et al (2016) and Fullhart et al (2018Fullhart et al ( , 2019, this method was initially referred to as dry soil bulk density optimization. However, we refer to the same methodology as fine-earth fraction optimization to avoid confusing soil bulk density as defined by Engda et al (2016) and Fullhart et al (2018Fullhart et al ( , 2019 with the usual definition of soil bulk density where the volume of coarse fragments is subtracted from the total subsurface region volume (e.g., Vincent & Chadwick, 1994; see also ;Fullhart et al, 2018).…”
Section: Fine-earth Fraction Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable isotope compositions of oxygen and hydrogen (δ 18 O and δ 2 H) in soil water are eco‐friendly indicators for water‐use strategies in plants, water transport, and evaporation (Engda et al, 2016; Fiipovic et al, 2014; Gebremeskel & Pieterse, 2007; He et al, 2017; Sprenger et al, 2016). However, a large spatial heterogeneity of the isotopic signal (Thomas et al, 2013; Yang et al, 2016) influenced by soil properties was detected, which hinders additional applications of isotopes in water.…”
Section: Introductionmentioning
confidence: 99%